At the forefront on nation building perspectives from the administrative and diplomatic service - Sheena Gurbakhash; Fiona Ghaus (Penerbit Universiti Teknologi Mara, 2014)
For anyone who has ever wondered about what really goes on behind the closed doors of Government, [this book] provides a fascinating insight into the backgrounds and thoughts of some of the men and women who rose to hold the highest positions in administration, their relationships with their political leaders, and their thoughts about the state of the nation.